State collaboration and development strategies in China : the case of the China-Singapore Suzhou Industrial Park, 1992-2002 - Pereira, Alexius A. (RoutledgeCurzon studies in the growth economies of Asia, 2003)
This book looks at Singapore and China to examine governmental collaboration on a foreign direct investment oriented strategy. Focusing on the unique collaborative venture, the Suzhou Industrial Park project, the author explores the economic, political and social relationships between Singapore and China throughout the course of the scheme as well as discussing why certain strategies were adopted, how they were implemented and their outcomes.